2008
DOI: 10.1007/s12325-008-0107-x
|View full text |Cite
|
Sign up to set email alerts
|

Review of third-and fourth-generation fluoroquinolones in ophthalmology: in-vitro and in-vivo efficacy

Abstract: Fourth-generation agents have increased potency against Gram-positive bacteria compared with levofloxacin, while maintaining similar potency against Gram-negative bacteria. Although levofloxacin 1.5% has demonstrated superior ocular penetration relative to gatifloxacin, the limited available data do not suggest this translates into superior clinical activity compared with moxifloxacin, which has significantly greater ocular penetration and better Gram-positive potency than gatifloxacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 40 publications
2
54
0
Order By: Relevance
“…Fourth-generation quinolones are important drugs used in ophthalmology and are more effective against Gram-positive bacteria compared to the other generations (Scoper, 2008;Stroman et al, 2005). This generation has also been demonstrated to be more active against mycobacteria and less affected by mutations in DNA gyrase .…”
Section: Introductionmentioning
confidence: 99%
“…Fourth-generation quinolones are important drugs used in ophthalmology and are more effective against Gram-positive bacteria compared to the other generations (Scoper, 2008;Stroman et al, 2005). This generation has also been demonstrated to be more active against mycobacteria and less affected by mutations in DNA gyrase .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that moxifloxacin would be preferable to cefuroxime because of its broader spectrum of action, better MIC levels and lower bacterial resistance. (O´Brien et al, 2007) (Scoper, 2008) (Jensen et al, 2008). Moxifloxacin is available as a self-preserved commercial ophthalmic formulation and requires no special preparation for intracameral therapy.…”
Section: Antibiotics Employed In the Operating Roommentioning
confidence: 99%
“…Coagulase-negative staphylococci (CoNS), including the most common species, Staphylococcus epidermidis, are the most frequently isolated organisms from culture-proven endophthalmitis cases (1,4,5). Topical fluoroquinolone agents (ciprofloxacin, ofloxacin, and levofloxacin) have been widely used as the first-line option for both prophylaxis and management of endophthalmitis and other ocular infections (6,7). However, recovery of ocular fluoroquinolone-resistant pathogens emerged soon after the introduction and widespread use of these agents in the 1990s and has significantly increased in the last 2 decades (7,8).…”
mentioning
confidence: 99%
“…The 8-methoxyfluoroquinolones, gatifloxacin (Zymar; Allergan) and moxifloxacin (Vigamox; Alcon), are the most frequent and widely used agents in ophthalmology due to their increased potency against Gram-positive pathogens and reduced rates of resistance compared with the older fluoroquinolones (6,7). Despite its withdrawal for systemic use, gatifloxacin is still available for topical ophthalmic use in well-tolerated eye drop formulations of 0.3% and 0.5%.…”
mentioning
confidence: 99%
See 1 more Smart Citation